Pancasila sebagai Paradigma Kehidupan dalam Bermasyarakat Bernegara - Kamdani Kamdani; Muhammad Dwi Ramadan; Muhammad Abdul Azis (Jurnal Kajian dan Penelitian Umum, 2025)
This research discusses Pancasila as the basis and guideline for national and state life in Indonesia. The main focus of this study is how Pancasila values ​​are implemented in everyday life to create a just, peaceful and prosperous society. This study also examines the role of Pancasila as a national development paradigm and as a value reference in facing social, political and cultural challenges in the modern era. By examining the values ​​of each principle, this research emphasizes the importance of strengthening the spirit of diversity, tolerance and social justice to maintain unity in diversity. This research uses a descriptive qualitative approach with a literature study method. Data was obtained through analysis of documents, books, scientific articles and other reliable sources relevant to the study of Pancasila as a paradigm for life. The analysis was carried out thematically by highlighting the five principles of Pancasila and their implementation in social life. This approach allows the identification of the core values ​​of Pancasila and their application in various aspects of life. Data validation is carried out through source triangulation to ensure the accuracy and relevance of the information.